Degradation of Anthraquinone Dye Reactive Blue 4 in Pyrite Ash Catalyzed Fenton Reaction - Milena Becelic-Tomin; Bozo Dalmacija; Ljiljana Rajic; Dragana Tomasevic; Djurdja Kerkez; Malcolm Watson; Miljana Prica (The Scientific World Journal)
Pyrite ash (PA) is created by burning pyrite in the chemical production of sulphuric acid. The high concentration of iron oxide, mostly hematite, present in pyrite ash, gives the basis for its application as a source of catalytic iron in a modified Fenton process for anthraquinone dye reactive blue 4 (RB4) degradation. The effect of various operating variables such as catalyst and oxidant concentration, initial pH and RB4 concentration on the abatement of total organic carbon, and dye has been assessed in this study. Here we show that degradation of RB4 in the modified Fenton reaction was efficient under the following conditions: pH=2.5; [PA]0=0.2 g L−1; [H2O2]0=5 mM and initial RB4 concentration up to 100 mg L−1. The pyrite ash Fenton reaction can overcome limitations observed from the classic Fenton reaction, such as the early termination of the Fenton reaction. Metal (Pb, Zn, and Cu) content of the solution after the process suggests that an additional treatment step is necessary to remove the remaining metals from the water. These results provide basic knowledge to better understand the modified, heterogeneous Fenton process and apply the PA Fenton reaction for the treatment of wastewaters which contains anthraquinone dyes.